TRANSFORMASI PESANTREN SALAF DALAM WAJAH MODERISASI - Galuh Prabowo; Rizqi Maulana Ilmi; Muh Khotibul Umam (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2024)
Pesantren is one of the oldest education systems in Indonesia. Islamic boarding school educational institutions are said to be a great tradition in studying religious knowledge by Muslims in this country. This great tradition takes the form of Islamic religious learning carried out by Muslim communities in Islamic boarding schools in Java. This research uses qualitative research methods to explore phenomena developing in Salaf Islamic boarding schools in the context of transformation. Qualitative research is used to examine events using a certain approach. Researchers deliberately determine research targets and subjects to be studied and studied to explore related phenomena that occur. Results and Discussion Based on the curriculum or education system used, Islamic boarding schools have three types, namely traditional/Salaf Islamic boarding schools, modern Islamic boarding schools, and comprehensive Islamic boarding schools. Traditional/Salaf Islamic boarding schools still maintain their original form with the teachings of books written by 15th century scholars using the language Arab. The teaching pattern is by applying the halaqah or mangaji tudang system which is carried out in mosques.